Utilisation of DNA barcoding in assessing the diversity of bats based on taxonomic records and identifying their plant-based diet in Peninsular Malaysia / Lim Voon Ching - Lim , Voon Ching (2018)
In Peninsular Malaysia, the diversity of bats was previously assessed through morphological identification of captured bats while the diet of plant-visiting bats were examined through morphological identification of seeds and pollen grains collected from bats. Yet morphological identification is often of limited service when applied to identification of morphologically similar bat and plant species. The objective of this research is to use a molecular approach, DNA barcoding to review the diversity of bats and their plant-based diet in Peninsular Malaysia. Through literature review and Neighbour-Joining analyses of DNA barcodes available from bats sampled in Peninsular Malaysia, at least 110 bat species have been documented in the region and eighteen of them are species complex which deserve further investigation. The diet of frugivorous bat, Cynopterus brachyotis, at secondary forest, oil palm plantation and urban area were compared by identifying pulps and seeds found in the bats’ faeces using DNA barcoding. Native and introduced plants were detected from bat faeces at all sampling sites, suggesting the dual role of C. brachyotis in dispersing (i) native plants which aid in forest regeneration, and (ii) introduced plants which potentially facilitate their invasion. The diet of nectarivorous bat, Eonycteris spelaea at urban area was examined by identifying the plant material present in the bat faeces using DNA metabarcoding. Many plant species which were detected from the bat faeces have not been reported in previous dietary studies of E. spelaea including ferns and figs, consequently suggesting that E. spelaea may not be specialised nectarivore. Therefore, the use of DNA barcoding has highlighted the taxonomic uncertainties in bats and provided new insights into diet of plant-visiting bats.